PERAN KEPALA SEKOLAH DALAM MENGAKOMODIR ASESMEN BERDIFERENSIASI PADA KURIKULUM MERDEKA DI SMA ISLAM AL-IANAH CIANJUR - Anwar, M. Saeful; Salamah, Dinda Siti; Nurapsi, Nurapsi; Suryadi, Rudi Ahmad (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
The education curriculum undergoes adjustments in various parts, especially when there is a learning loss during the COVID-19 pandemic, this is characterized by a learning crisis experienced by students. The purpose of this study was to determine the Role of the school leader In recommending the learning assessment of Islamic age education in the early curriculum at Islam al-ianah Cianjur High School. The method used in this research is a qualitative research method, the data collection techniques used are interviews, observation, and documentation. the data analysis techniques used are data reduction, data display, and conclusion drawing/verification. Several factors that influence the implementation of assessment by the mandate of the curriculum revolve around external and internal factors. External factors that influence the implementation of differentiated assessment include: (1) lack of technical guidance from related agencies to teachers (2) changes in terms of the independent curriculum are considered too fast (3) the independent teaching platform provided by the government tends to be wordy and less applicable (4) differences between public schools and private schools in various policies provided, one of which is differences in welfare. Internal factors include (1) teachers' lack of mastery of IT, (2) teachers' lack of literacy regarding the concept and mapping of the independent curriculum, and (3) teachers' old mindset regarding learning and the assessment process.